2015
DOI: 10.1159/000368291
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 Ibritumomab Tiuxetan Followed by Rituximab Maintenance as Treatment for Patients with Diffuse Large B-Cell Lymphoma Are Not Candidates for Autologous Stem Cell Transplant

Abstract: Background: Not all patients with diffuse large B-cell lymphoma (DLBCL) are candidates for aggressive regimens. 90Y ibritumomab tiuxetan (90Y-IT), an anti-CD20 radionuclide-conjugated antibody, has demonstrated clinical efficacy in DLBCL with a favorable toxicity profile. Methods: This phase II trial investigated the overall response rate (ORR), event-free survival (EFS), overall survival (OS) and toxicity of treatment with 90Y-IT (0.4 or 0.3 mCi 90Y/kg based on plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Thirty-three studies aimed to investigate the association between platelet counts and bleeding but could not be included, as no bleeding events occurred during the study period. 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 Thus, 52 studies were included for quality assessment and data extraction. 2 …”
Section: Resultsmentioning
confidence: 99%
“…19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Thirty-three studies aimed to investigate the association between platelet counts and bleeding but could not be included, as no bleeding events occurred during the study period. 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 Thus, 52 studies were included for quality assessment and data extraction. 2 …”
Section: Resultsmentioning
confidence: 99%
“…Treatments in the ASCT-ineligible studies were grouped as follows: (1) CAR T-cell therapy [ 5 , 32 ], including axicabtagene ciloleucel [ 8 ], lisocabtagene maraleucel [ 10 ], and tisagenlecleucel [ 9 ]; (2) chemotherapy, including R-Gemox (gemcitabine and oxaliplatin) [ 33 , 34 ], R-B (bendamustine) [ 14 , 35 38 ], pixantrone [ 39 ], one of the various chemotherapies [ 39 ] (one of vinorelbine, oxaliplatin, ifosfamide, etoposide, mitoxantrone, gemcitabine, or rituximab), R-ifosfamide+etoposide [ 40 ], R-pixantrone [ 41 ], R-gemcitabine [ 41 ], R-PECC (prednisolone, etoposide, chlorambucil, and lomustine) [ 42 ], decitabine plus DHAP [ 43 ], ibrutinib plus lenalidomide plus R-EPOCH (etoposide, prednisolone, vincristine, cyclophosphamide, and doxorubicin) [ 44 ], pixantrone plus obinutuzumab [ 45 ], and lenalidomide plus R-GDP [ 46 ]; (3) ibrutinib-based therapy, including ibrutinib plus durvalumab [ 47 ], ibrutinib plus nivolumab [ 48 ], and ibrutinib monotherapy [ 49 ]; (4) lenalidomide-based therapy, including R-lenalidomide [ 50 ], lenalidomide monotherapy [ 34 ], obinutuzumab plus lenalidomide [ 51 ], and temsirolimus plus lenalidomide [ 52 ]; (5) loncastuximab tesirine [ 17 ]; (6) polatuzumab plus bendamustine and rituximab [ 14 , 53 , 54 ] and R-polatuzumab [ 55 ]; (7) selinexor [ 15 ]; (8) tafasitamab, including tafasitamab monotherapy [ 56 ] and tafasitamab plus lenalidomide [ 16 ]; (9) others, including ibritumomab [ 57 , 58 ], temsirolimus [ 59 ], ofatumumab [ 60 ], R-everolimus [ …”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are two approved RTX agents for use in B-cell lymphoma: 131 I-tositumomab (Bexxar Ò , GlaxoSmithKline) and 90 Y-ibritumomab tiuxetan (ZevalinÒ, Spectrum) [140]. Several clinical Phase III trials have shown the utility of those agents in treatment of B-cell NHLs [9, [141][142][143]. Unfortunately, 131 I-tositumomab has recently been discontinued by the GlaxoSmithKline (NYSE: GSK) because of low profits.…”
Section: Other Anti-cd20 Moabsmentioning
confidence: 99%